2020
DOI: 10.1007/s13238-020-00723-9
|View full text |Cite
|
Sign up to set email alerts
|

Loss of 4.1N in epithelial ovarian cancer results in EMT and matrix-detached cell death resistance

Abstract: Epithelial ovarian cancer (EOC) is one of the leading causes of death from gynecologic cancers and peritoneal dissemination is the major cause of death in patients with EOC. Although the loss of 4.1N is associated with increased risk of malignancy, its association with EOC remains unclear. To explore the underlying mechanism of the loss of 4.1N in constitutive activation of epithelial-mesenchymal transition (EMT) and matrix-detached cell death resistance, we investigated samples from 268 formalin-fixed EOC tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…An interesting link between loss of cellular adhesion to extracellular matrix, cancer progression and entosis was found in the case of epithelial ovarian cancer (EOC) [ 31 ]. An analysis of 268 archived paraffin-embedded samples found that loss of the 4.1N protein was associated with more malignant phenotype and worse prognosis.…”
Section: Entosis In Cancermentioning
confidence: 99%
“…An interesting link between loss of cellular adhesion to extracellular matrix, cancer progression and entosis was found in the case of epithelial ovarian cancer (EOC) [ 31 ]. An analysis of 268 archived paraffin-embedded samples found that loss of the 4.1N protein was associated with more malignant phenotype and worse prognosis.…”
Section: Entosis In Cancermentioning
confidence: 99%
“…The result from the nude mice model suggests a suppressor role of 4.1N in a unique interesting peritoneal dissemination that is different from lymph node or blood metastases in other cancers ( Xi et al, 2013 ; Wang et al, 2020a ). A previous study proposed that 4.1N suppresses EOC’s intraperitoneal dissemination by regulating 4.1N-interacting adhesion molecules and the F-actin cytoskeleton during the epithelial–mesenchymal transition (EMT) ( Wang et al, 2020a ). Besides, in EOC, a suppressor role of 4.1N in hypoxia-induced EMT and related genes has been demonstrated.…”
Section: 1n In Cancersmentioning
confidence: 83%
“…The loss of 4.1N expression is more related to type II rather than type I EOCs ( Xi et al, 2013 ). 4.1N loss is significantly correlated with a poorer differentiation and aggressive behavior, increased clinical stage progression, lower response to first-line chemotherapeutic treatment, poor overall survival, and progression-free survival in EOC patients ( Xi et al, 2013 ; Wang et al, 2020a ). The result from the nude mice model suggests a suppressor role of 4.1N in a unique interesting peritoneal dissemination that is different from lymph node or blood metastases in other cancers ( Xi et al, 2013 ; Wang et al, 2020a ).…”
Section: 1n In Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Carcinoma cells that acquire a mesenchymal-like phenotype through EMT are more resistant to cell death [ 31 ], and numerous studies have shown a correlation between EMT and chemotherapy resistance [ 32 , 33 ]. For example, in lung carcinoma, EMT can elicit resistance to newly developed targeted therapeutics such as alectinib, ceritinib, and lorlatinib in lung tumors associated with ALK translocations, suggesting EMT as a mechanism leading to drug resistance [ 34 ].…”
Section: Carcinoma Cell Plasticity Contributes To Therapy Evasion and Stemnessmentioning
confidence: 99%